Die Speichergruben der späturnenfelderzeitlichen Wallanlage von Stillfried an der March (Niederösterreich) Von der Getreidelagerung bis zur profanen oder kultischen Verfüllung - Griebl, Monika (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
In this publication, the characteristic bell-shaped pits are investigated from initial use as storage facilities for grain to the final backfilling process. The study demonstrates that the "central site" of Stillfried also served as a large grain storage place in the Late Bronze Age (Urnfield culture). The observed backfill patterns in the abandoned pits suggest profane or religiously motivated rules imposed by a legislative authority.